Using Locusta Migratoria as a Nitrogen Source for the Growth and Development of Microorganisms - Esabi Başaran Kurbanoğlu; Perihan Akbaş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Characteristics and the use as culture media of protein hydrolysate from Locusta migratoria were determined in comparison with different peptones. After powdering, it was hydrolyzed chemically (acid hydrolysis) and obtained product Locust Peptone (LP). The contents of protein, fat, nitrogen, ash, minerals, total sugars and amino acids of LP were determined and it was seen that it has both organic and inorganic materials enough to use as a component of the medium. The effects of different concentrations added 20g/l glucose of LP on the growth of four test bacteria (Escherichia coli, Bacillus subtilis, Pseudomonas putida and Staphylococcus aureus) and test yeasts (Rhodotorula glutinis, Candida albicans, Saccharomyces cerevisiae) were investigated and it was found that the optimal concentration for bacteria and yeast are %0,6 and LP was compared with bacteriological peptone (BP), fish peptone (FP) and meat peptone (MP) .The obtained results with surface streaking and shaking culture procedures showed that LP yielded a little higher or equal FP and BP in both normal bacteria, but these values were lower than values obtained from MP. The results show that LP performed similar to or even better than commercial peptones as nitrogen sources for microorganisms growth. A new peptone has been developed from locust for microbiological media in the present study.